Orientacja na testy w szkolnictwie współczesnym – kontrowersje ideologiczne i pedagogiczne - Gromkowska-Melosik, Agnieszka (Wydawnictwo Naukowe UAM, 2015)
The purpose of the article is reconstruction of the problem of ideological and social controversies surrounding the growing importance of the tests in determining the boundaries of contemporary neoliberal school reality. There is no doubt that in recent years the focus of the test-driven policies applied in the context of both formal and social criteria for evaluating students and schools has shifted decisively towards tangible results associated with the tests results. You can even tell that the phenomenon of "testing obsession" has dominated everyday life of the school and the identity of the students and has replaced student-centering learning. The author of the article considers these problems against the background of theory and reality.
Tests Oriented Education in Contemporary Schooling – Ideological and Pedagogical Controversies
Keywords: tests; neoliberalism; culture of testing; student-centered learning; test-driven policies